2010
DOI: 10.1029/2009ja014750
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the source of terrestrial neutron bursts detected in thunderstorm atmosphere

Abstract: [1] To localize an altitude of the neutron source responsible for the neutron flux enhancements observed on the ground, numerical simulations of photonuclear production and transport to on-ground detector locations were carried out. The neutron fluence calculated for the volumetric source located at the altitudes 8-12 km is consistent with that estimated from neutron numbers measured on the ground. This altitude range is consistent with the idea that the burst of hard g rays detected recently by Tsuchiya et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 37 publications
4
29
0
1
Order By: Relevance
“…These neutron spectra suggest that the neutrons arriving at the observatory have a mean energy of 1-10 MeV and the maximum energy of produced neutrons is about onethird of that of the rays emitted from a source. The former feature has been reported by Carlson et al [17] and Babich et al [31] as well. Figure 7 represents spectra for rays and electrons assuming the isotropic emission of initial rays.…”
Section: B Energy Spectrumsupporting
confidence: 60%
See 1 more Smart Citation
“…These neutron spectra suggest that the neutrons arriving at the observatory have a mean energy of 1-10 MeV and the maximum energy of produced neutrons is about onethird of that of the rays emitted from a source. The former feature has been reported by Carlson et al [17] and Babich et al [31] as well. Figure 7 represents spectra for rays and electrons assuming the isotropic emission of initial rays.…”
Section: B Energy Spectrumsupporting
confidence: 60%
“…According to Babich et al [31], a yield rate of a photonuclear neutron per one gamma ray with energies >10 MeV is 4:3 Â 10 À3 . Produced neutrons propagate in the atmosphere, attenuated by elastic and/or inelastic collisions with air nulcei.…”
Section: Neutron Production and Propagation In The Airmentioning
confidence: 99%
“…However, they also found that the neutron flux in Earth orbit from an upward TGF was far too small to explain the events seen by Bratolyubova-Tsulukidze et al (2004). Babich et al (2010b) estimated neutron production for runaway avalanches in the high-field volume of a thunderstorm. While not explicitly calling this a simulation of a TGF, the simulated event duration (<3.5 ms) and derived gamma-ray flux suggest that this is essentially also a downward-TGF model.…”
Section: Interpretation Of Neutron Observationsmentioning
confidence: 99%
“…On the other hand, it is possible that RREA, either with or without significant relativistic feedback, acting on the ambient cosmic-ray flux could discharge the large scale thunderstorm field in such a way that local electric field enhancements occur, potentially providing a high enough field region to allow lightning to initiate, possibly with the help of hydrometeors (Dwyer 2005b;Babich et al 2011a). Figure 28 shows how RREAs can discharge the large scale field producing localized field enhancements (also see Petersen et al 2008).…”
Section: Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation